Bioprospecting study of cultivable prokaryotic fraction from Manaure solar saltern, La Guajira, Colombia (2019)
The objective of this research was to establish the bioprospecting potential of the cultivable bacteria isolated from the Manaure Solar Saltern in La Guajira, Colombia. To achieve this, a strategy of mixed cultures was implemented to evaluate the cytotoxic and antibacterial activity of their crude extracts. The best bioactive mixed culture was selected, and their isolates were obtained and characterized. The results from the biological assays with the crude extracts of the isolates grown individually led to establish that the halophilic bacterium Vibrio diabolicus A1SM3 was responsible for the biological activity of the mixed culture. From the bioguided fractionation of this extract and its analysis by HPLC-MS/MS and NMR, the isotrisindoline was identified as the compound responsible for the cytotoxic and antibacterial activity. After that, variations on the carbon and nitrogen source, and the salinity of the medium were made to determine how they affected the isotrisindoline production. The MS/MS data obtained from the crude extracts of these cultures were analyzed through molecular networking in order to establish the effect of these variations. In addition to this, it was possible to identify that this microorganism produces polyhydroxybutyrates, a biopolymer widely produced and accumulated by Vibrio species with great applications in the plastics industry. Finally, by sequencing the genome of Vibrio diabolicus A1SM3, the biosynthetic gene cluster associated with the production of this biopolymer was annotated.